Chain of Values: Examining the Economic Impacts of Blockchain on the Value-Added Tax System - Cho, Soohyun; Lee, Kyungha (Kari); Cheong, Arion; No, Won Gyun; Vasarhelyi, Miklos A. (Journal of Management Information Systems, 2021)
Blockchain technology can benefit inter-organizational activities by improving data integrity, increasing transaction transparency, and decreasing transaction costs. In this paper, we discuss the strategic and economic value of this technology by applying it to the value-added tax (VAT) reporting system, focusing on blockchain’s characteristic traceability. By effectively increasing financial transparency, the application of blockchain to the VAT system can prevent VAT-related fraud (e.g., underreported VAT) that can arise due to the information asymmetry that exists at different stages of the supply chain. We develop a game theoretical model that involves a retailer and two vendors in order to study the players’ strategic decisions regarding blockchain adoption and to examine the effects on social welfare. We also show how the decision to adopt blockchain depends on considerations such as adoption costs, the vendors’ VAT reporting behavior, the retailer’s profit margins, and inter-vendor competition. Furthermore, we find that under certain conditions, policymakers can increase social welfare by providing subsidies to encourage blockchain adoption.88 Sun Yin, H.H.; Langenheldt, K.; Harlev, M.; Mukkamala, R.R.; and Vatrapu, R. Regulating cryptocurrencies: A supervised machine learning approach to de-anonymizing the bitcoin blockchain. Journal of Management Information Systems, 36, 1 (2019), 37–73.[Taylor & Francis Online], [Web of Science ®] , [Google Scholar]